2018
DOI: 10.3390/molecules23010121
|View full text |Cite
|
Sign up to set email alerts
|

VSP-17, a New PPARγ Agonist, Suppresses the Metastasis of Triple-Negative Breast Cancer via Upregulating the Expression of E-Cadherin

Abstract: Triple-negative breast cancer (TNBC), an aggressive subtype of breast cancer, shows higher metastases and relapse rates than other subtypes. The metastasis of TNBC is the main reason for the death of TNBC patients. Increasing evidence has shown that inhibiting the metastasis of TNBC is a good method for TNBC treatment. Here, VSP-17 was designed and synthesized as an agonist of PPARγ, evidenced by upregulating the expression of CD36 and increasing the activity of PPARγ reporter gene. VSP-17 obviously inhibited … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 32 publications
(31 reference statements)
0
14
0
Order By: Relevance
“…VSP-17 (C 23 H 18 F 3 N 3 O, MW: 409.1402, purity ≥98%) was designed and synthesized by our team (Guangxi Colleges and Universities Key Laboratory of Pharmacology), the details of which have been described in our previous study ( 28 ). siAMPK (cat.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…VSP-17 (C 23 H 18 F 3 N 3 O, MW: 409.1402, purity ≥98%) was designed and synthesized by our team (Guangxi Colleges and Universities Key Laboratory of Pharmacology), the details of which have been described in our previous study ( 28 ). siAMPK (cat.…”
Section: Methodsmentioning
confidence: 99%
“…E-cadherin is a key marker of EMT (30). A previous study reported that VSP-17 treatment could upregulate the mRNA expression levels of E-cadherin in TNBC cells (28). To further determine the relationship between the activation of AMPK and the inhibition of the EMT process by VSP-17, MDA-MB-231 and MDA-MB-453 cells were treated with VSP-17 (10 µM) in combination with compound C (1 µM) or siAMPK transfection, respectively.…”
Section: Vsp-17 Treatment Suppresses the Migration And Invasion Of Tnmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, a PPAR- γ agonist—rosiglitazone—reduces migration of both CAFs and breast cancer cells [ 121 ]. In addition, a novel PPAR- γ agonist VSP-17 inhibits TNBC metastasis via induction of E-cadherin [ 122 ]. Thymoquinone (TQ) is another compound that blocks CXCR4 expression in TNBC cells.…”
Section: Cxcl12/cxcr4-targeted Therapies Against Breast Cancermentioning
confidence: 99%